Exotic structure and decay of medium mass nuclei near the drip lines - Petrovici, A. (HNPS Advances in Nuclear Physics, 2019)
Properties of medium mass nuclei near the drip lines are not only relevant for nuclear structure, but are of high interest in nuclear astrophysics and in several applications, in particular nuclear technology. Shape coexistence effects play an essential role in the structure and dynamics of proton-rich A∼70 nuclei and neutron-rich A∼100 nuclei. Results concerning a self-consistent description of exotic phenomena including Gamow-Teller β-decay of proton-rich nuclei, triple shape coexistence and shape evolution in the N=58 Sr and Zr isotopes as well as Gamow-Teller β-decay strength distributions and structure properties of neutron- rich nuclei relevant for reactor decay heat obtained in the frame of the complex Excited Vampir model using realistic effective interactions in large model spaces will be presented.